Sketches New and Old, Part 3. - Twain, Mark, 1835-1910 (Salt Lake City, UT : Project Gutenberg, 2004)
"Sketches New and Old, Part 3." by Mark Twain is a section of a short story collection published in 1875. This gathering of mostly fictional tales showcases Twain's characteristic wit and humor across diverse subjects. From ghost stories to political satire, agricultural mishaps to bizarre dreams, these sketches reveal the author's sharp eye for human folly and social absurdity. The collection captures American life through comedic observations and imaginative narratives that entertain while gently mocking society's pretensions. (This is an automatically generated summary.)
Disgraceful persecution of a boy -- The judge's "spirited woman" -- Information wanted -- Some learned fables, for good old boys and girls -- My late senatorial secretaryship -- A fashion item -- Riley, Newspaper correspondent -- A fine old man -- Science vs. luck.
Wikipedia page about this book: https://en.wikipedia.org/wiki/Sketches_New_and_Old
Release date is 2004-06-26
Produced by David Widger
Keywords: Humorous stories, American; United States -- Social life and customs -- Fiction